Growth attributes and biochemical composition of Padina pavonica (L.) from the Red Sea, in response to seasonal alterations of Tabuk, Saudi Arabia - Abid Ali Ansari; Sulaiman Mohammad Ghanem (Egyptian Journal of Aquatic Research, 2019)
In the following research we studied the seasonal pattern of biomolecule accumulation, content of mineral ashes, macronutrient assimilation and activity of superoxide dismutase, catalase and peroxidase in a brown marine alga Padina pavonica from the study site at Haql, Red Sea. The total protein, carbohydrate and lipid contents were highest in the month of July. The values for mineral ashes, macronutrients and dietary fibers were also high in this month suggesting that the algae is in vegetative phase and this is the best time for harvesting. We studied the changes in enzymatic activity and proline accumulation to correlate with the seasonal stress response in P. pavonica. Significantly higher values for three studied antioxidant enzymes and increased proline accumulation in January suggest stress response. Considering the growing demands for application of algae in food and industry, the present study put forward useful information for the development of P. pavonica as a good option. The pristine natural reserves of the Gulf of Aqaba are important in this regard. There is a need to develop methods and techniques to obtain maximal benefits from these resources. Keywords: Antioxidants, Algal growth, Red Sea, Seasonal variations